"Rainbow Draws" in the Emergency Department: Clinical Utility and Staff Perceptions. (19th November 2019) - Snozek, Christine L H; Hernandez, James S; Traub, Stephen J
Abstract: Background: Collecting a predefined set of blood tubes (the "rainbow draw") is a common but controversial practice in many emergency departments (EDs), with limited data to support it. We determined the actual utilization of rainbow draw tubes at a single facility and evaluated the perceptions of ED staff regarding the utility of rainbow draws. Methods: We analyzed 2 weeks of ED visits (1326 visits by 1240 unique patients) to determine blood tube utilization for initial and add-on testing, as well as the incidence of additional venipunctures. We also surveyed ED staff regarding aspects of ED phlebotomy and test ordering. Utilization data analysis was structured to satisfy specific concerns addressed in the ED staff survey. Results: Observed tube utilization data showed that fluoride/oxalate, citrate, and serum separator tubes were frequently discarded unused, and that the actual utility of the rainbow draw for add-on testing and avoiding additional venipunctures was low. ED staff perceived that the rainbow draw was highly valuable, both to expedite add-on testing and to avoid additional venipunctures. Contrasting the objective (utilization data) and subjective (survey results) to drive changes in the standard ED blood collection reduced the estimated waste blood by 175 L/year. Conclusions: Comparison of perceptions and objective utilization data drove process changes that were mutually agreeable to ED and laboratory staff. Although specifics of ED and laboratory work flows vary between institutions, the principles and strategy of this study are widely applicable.